The Emergence and Development of Dialectical Views in the Avesta - Shokirov Murod Rustamovich (International Journal on Integrated Education, 2026)
In this article, reference is made to the Avesta—the most ancient source of our people, invaluable in its educational significance, enriching thought with the truths of life and an attempt is made to show its importance in developing philosophical knowledge about the universe. The value of the Avesta from a philosophical point of view lies in the fact that it attempts to explain all things, phenomena, and processes in the world dialectically.